Analyzing the Effects of Key Design Factors of a Negative-Differential-Resistance (NDR) Microfluidic Oscillator – An Equivalent-Circuit-Model Approach (Advances in Applied Mathematics and Mechanics, 2022)
Numerical study on dynamic hydroelastic problems is usually rather complex due to the coupling of fluid and solid mechanics. Here, we demonstrate that theperformance of a hydroelastic microfluidic oscillator can be analyzed using a simpleequivalent circuit model. Previous studies reveal that its transition from the steadystate to the oscillation state follows the negative-differential-resistance (NDR) mechanism. The performance is mainly determined by a bias fluidic resistor, and a pressure-variant resistor which further relates to the bending stiffness of the elastic diaphragmand the depth of the oscillation chamber. In this work, a numerical study is conductedto examine the effects of key design factors on the device robustness, the applicablefluid viscosity, the flow rate, and the transition pressure. The underlying physics is interpreted, providing a new perspective on hydroelastic oscillation problems. Relevantfindings also provide design guidelines of the NDR fluidic oscillator.